2021
DOI: 10.5713/ajas.20.0288
|View full text |Cite
|
Sign up to set email alerts
|

Broken rice in a fermented total mixed ration improves carcass and marbling quality in fattened beef cattle

Abstract: Broken rice in a fermented total mixed ration improves carcass and marbling quality in fattened beef cattle ABSTRACT Objective: This study aimed to determine the effects of replacing cassava chips with broken rice in a fermented total mixed ration diet on silage quality, feed intake, ruminal fermentation, growth performance, and carcass characteristics in the final phase of fattening beef cattle. Methods: Eighteen Charolais-Thai native crossbred steers (average initial body weight: 609.4 ± 46 kg; average age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…Intramuscular fat (IMF) is an important constituent of meat and affects its edibility (Brand et al, 2018 ). It has been demonstrated that the forage proportion in the diet affects the IMF content (Kotupan and Sommart, 2021 ). In the present investigation, intramuscular fat in lambs supplemented with AH was greater than that of the OH group.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular fat (IMF) is an important constituent of meat and affects its edibility (Brand et al, 2018 ). It has been demonstrated that the forage proportion in the diet affects the IMF content (Kotupan and Sommart, 2021 ). In the present investigation, intramuscular fat in lambs supplemented with AH was greater than that of the OH group.…”
Section: Discussionmentioning
confidence: 99%
“…Rice byproducts are abundant agricultural products, including straw, bran, and broken rice [6]. Nutritional values of broken rice have dry matter (DM) of 86.9% to 93.6%, ash, crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), and starch within the ranges of 0.4% to 5.0%, 3.1% to 10.2%, 0.5% to 2.2%, 0.8% to 9.3%, 0.6% to 2.5%, and 70.8% to 87.8% of DM, respectively [7][8][9][10][11][12][13]. The gross energy ranges from 14.7 to 15.6 MJ/kg [11][12][13] and ME 7.9 to 12.7 MJ/kg [7,9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional values of broken rice have dry matter (DM) of 86.9% to 93.6%, ash, crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), and starch within the ranges of 0.4% to 5.0%, 3.1% to 10.2%, 0.5% to 2.2%, 0.8% to 9.3%, 0.6% to 2.5%, and 70.8% to 87.8% of DM, respectively [7][8][9][10][11][12][13]. The gross energy ranges from 14.7 to 15.6 MJ/kg [11][12][13] and ME 7.9 to 12.7 MJ/kg [7,9,10,12]. Therefore, broken rice has excellent nutrient quality and is a locally available year-round feed resource in Thailand [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demand for such high-quality beef is increasing due to its higher price than local beef. However, the productivity of fattened beef cattle in developing tropical countries has been low due to the animals’ genetic profiles and the provision of feeds and feeding systems based on available low-quality agricultural by-products, such as rice straw [ 2 ].…”
Section: Introductionmentioning
confidence: 99%